Large-Scale Food Fortification and Biofortification in Low- and Middle-Income Countries: A Review of Programs, Trends, Challenges, and Evidence Gaps. Issue 2 (June 2018) - Osendarp, Saskia J. M.; Martinez, Homero; Garrett, Greg S.; Neufeld, Lynnette M.; De-Regil, Luz Maria; Vossenaar, Marieke; Darnton-Hill, Ian
Background: Food fortification and biofortification are well-established strategies to address micronutrient deficiencies in vulnerable populations. However, the effectiveness of fortification programs is not only determined by the biological efficacy of the fortified foods but also by effective and sustainable implementation, which requires continual monitoring, quality assurance and control, and corrective measures to ensure high compliance. Objective: To provide an overview of efficacy, effectiveness, economics of food fortification and biofortification, and status of and challenges faced by large-scale food fortification programs in low- and middle-income countries (LMIC). Methods: A literature review of PubMed publications in English from 2000 to 2017, as well as gray literature, targeting nongovernmental organizations whose work focuses on this topic, complemented by national reports and a "snowball" process of citation searching. The article describes remaining technical challenges, barriers, and evidence gap and prioritizes recommendations and next steps to further accelerate progress and potential of impact. Results: The review identifies and highlights essential components of successful programs. It also points out issues that determine poor program performance, including lack of adequate monitoring and enforcement and poor compliance with standards by industry. Conclusions: In the last 17 years, large-scale food fortification initiatives have been reaching increasingly larger segments of populations in LMIC. Large-scale food fortification and biofortification should be part of other nutrition-specific and nutrition-sensitive efforts to prevent and control micronutrient deficiencies. There are remaining technical and food system challenges, especially in relation to improving coverage and quality of delivery and measuring progress of national programs.